'Long COVID' syndrome. Issue 4 (19th April 2021) - Taribagil, Priyal; Creer, Dean; Tahir, Hasan
Abstract : SARS-CoV-2 has resulted in a global pandemic and an unprecedented public health crisis. Recent literature suggests the emergence of a novel syndrome known as 'long COVID', a term used to describe a diverse set of symptoms that persist after a minimum of 4 weeks from the onset of a diagnosed COVID-19 infection. Common symptoms include persistent breathlessness, fatigue and cough. Other symptoms reported include chest pain, palpitations, neurological and cognitive deficits, rashes, and gastrointestinal dysfunction. We present a complex case of a previously well 28-year-old woman who was diagnosed with COVID-19. After resolution of her acute symptoms, she continued to experience retrosternal discomfort, shortness of breath, poor memory and severe myalgia. Investigations yielded no significant findings. Given no alternative diagnosis, she was diagnosed with 'long COVID'.